Proclaiming the Gospel in the Midst of Pluralism: Contextual Evangelism Strategies in Jayapura-Papua - Yanto Minggu, Trisno; Labobar, Yohanes Kristian (REI MAI: Jurnal Ilmu Teologi dan Pendidikan Kristen, 2025)
The aims of this research is to formulate evangelistic strategies and explores the internal and external challenges in the Indonesian especially in Jayapura-Papua context. The method used is qualitative with interview techniques with pastors, evangelists, and congregation elders. Data analysis uses the Miles and Huberman model, namely through reduction, presentation of data in tables, and drawing conclusions. The results of the study show that evangelism in Indonesia faces various obstacles in three areas: cultural, social, and political. Internal challenges in the cultural field include a lack of understanding of contextual theology and the application of gospel inculturation, while external challenges are in the form of cultural diversity and rejection of Christian symbols. In the social sphere, the internal is the division between denominations, while the external is majority pressure and a negative stigma against evangelism. In the political field, internal challenges are in the form of a lack of church synergy in responding to regulations, while external challenges include legal restrictions and intolerance. This research shows the evangelistic strategies that integrate understanding of local culture with adaptive theological reflection. This is effective in answering challenges and conveying the gospel in a relevant way in the midst of the plurality of Jayapura society